Exploring the molecular mechanism of Gan Shuang granules for the treatment of non-alcoholic steatohepatitis using network pharmacology, molecular docking, and experimental verification - Zhi, Guoguo; Shao, Bingjie; Zheng, Tianyan; Mu, Jie; Li, Jingwei; Feng, Yiyuan; Zhu, Sha; Dang, Yanni; Liu, Feng; Wang, Dong (Frontiers in Pharmacology, 2023)
Background: With the gradual increase in prevalence in recent years, non-alcoholic steatohepatitis (NASH) has become one of the significant health problems that urgently needs to be addressed worldwide. GanShuang Granules (GSG) is derived from the classical Chinese formula Xiaoyao San and mainly used in the clinical treatment of chronic liver diseases. Objective: In this study, we aim to gain a deeper insight into the inhibiting effects of GSG on non-alcoholic fatty liver disease (NAFLD) rats and preliminarily elucidate the underlying intervention mechanisms. Methods: First, High performance liquid chromatography (UHPLC-Q/Orbitrap-MS/MS) was used for the active compounds prediction in GSG. Then the data was mapped to mzCloud database. The targets corresponding to GSG compounds were collected from public databases, along with disease genes for NAFLD. The core targets and molecular mechanisms of GSG for NAFLD treatment were predicted by protein-protein interaction (PPI) network, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional enrichment analyses. Molecular docking of the core target-component interactions was simulated using AutoDock Vina software. The effect of GSG on NASH rats was evaluated by pathological staining and analysis of various index results. Finally, the candidate targets were further validated by ELISA and western blot (WB) analyses. Results: Combining UHPLC-Q/Orbitrap-MS/MS data analysis and public database data, a total of 346 cross-targets were obtained, corresponding to 81 compounds. The subnetwork with an MCODE score of 53.623 is a potential core target group for this study. GO and KEGG enrichment analyses showed that the targets of GSG in NAFLD were mostly related to oxidative stress, the NF-κB signaling pathway, and the apoptosis signaling pathway. By integrating the results of network pharmacology analysis, the core objectives of this study mainly include AKT1, CASP9, TNF, and CASP8. The core ingredients are related to resveratrol and fisetin. The molecular docking results indicated key binding activity between AKT1-fisetin, AKT1-Resveratrol, and CASP8-fisetin. Moreover, GSG could improve the inflammatory status and restore the abnormal lipid accumulation of NAFLD/NASH liver, and these levels are further verified by pathological staining and detection of related indicators. Mechanistically, GSG could regulate protein expression levels in the liver for P65, p-P65, IKB, p-IKB, IKK, caspase-3, -8, -9, and cytochrome C, etc. It reflects the inhibitory effect of GSG on the NF-κB/IκB signaling pathway. Conclusion: Our results suggested that GSG demonstrated therapeutic effects on NAFLD/NASH rats, and these may be mainly reflected in the inhibitory effects on the NF-κB/IκB signaling pathway and its downstream inflammation and apoptosis signals.